Implications of Public Housing Policies in Singapore and Australia for China - Xu, Zhuangsi (Faculty of Law, Universitas Brawijaya, 2025)
This paper delves deeply into the experiences and lessons of public housing policies in Singapore and Australia as points of references for China’s housing policies. By drawing on the experiences of these countries this paper hopes to innovate policy tools to promote the fair, efficient and sustainable development of an affordable housing system. Singapore and Australia tackle the housing problem from very different angles highlighting that the success of public housing policies depends on an organic combination of scientific policy design, legal guarantees, dynamic management, and effective implementation. The paper will adopt a policy-oriented research on the effective housing policies of Singapore and Australia for improving and optimizing China's housing security. Ultimately, China should legislate a Housing Security Law, clarify central-local responsibilities, and secure land and finance, drawing on Singapore’s land acquisition and provident fund models; establish a national housing-demand database for dynamic matching, adopt Singapore’s tiered supply and Australia’s targeted subsidies to broaden and differentiate support; and build an inter-agency data platform to enhance eligibility screening, ensuring efficient and equitable affordable housing allocation.